Alat Komunikasi Pemasaran, Hubungan Emosional, dan Pilihan Merek: Bukti dari Industri Makanan Sehat - Pepey Kurnia; Phillipe Stuart Lepar; Rike Penta Sitio (International Journal of Digital Entrepreneurship and Business, 2023)
This research examines the effects of information sharing, peer pressure, and entertainment on attitude towards a brand. In addition, this research also examines the effects of entertainment on emotional connection, emotional connection on purchase intention, and attitude towards a brand on purchase intention. This research uses SEM (Structural Equation Modelling) method and LISREL version 8.80 as tools for data analysis. The population is people in the city of Jakarta. The number of respondents in this research amounts to 165 people. The respondents taken in this research are those familiar with healthy food of FMCG (Fast Moving Consumer Goods) type and have seen healthy food advertisements on social media. Then, this study uses quantitative methods and a hypothesis-testing approach. Firstly, information sharing has no significant effect on attitude towards a brand, unlike peer pressure having a significant effect on attitude towards a brand. Furthermore, entertainment also considerably affects the attitude towards a brand as much as it does emotional connection. Finally, attitude towards a brand has a significant effect on purchase intention. The research findings indicate that peer pressure and entertainment influence the attitude toward a brand, while information sharing does not significantly influence the attitude toward a brand. The effects of entertainment on emotional connection, emotional connection on purchase intention, and attitude towards a brand on purchase intention are significant. To reinforce purchase intention, it is suggested that entertainment and emotional marketing be maximally utilized due to the amount of influence these could generate.